Antidiabetes Activity of Ethanol Extract of Pandan Leaves (Pandanus amaryllifolius Roxb) in Male White Mice (Mus musculus) - Jehan, Nabilah Nauli; Hidayah, Harismayanti; Khairani, Ayudia Cipta (Journal of Islamic Pharmacy, 2025)
Diabetes Mellitus is a metabolic disease characterized by hyperglycemia due to abnormalities in insulin secretion. This study aims to evaluate the antidiabetic effect of ethanol extract of fragrant pandan leaves (Pandanus ammarillyfolius Roxb) on aloxane-induced male white mice (Mus musculus). After alloxane induction, all test animals reached hyperglycemic conditions with blood glucose levels of ≥126 mgdL. The method used was the Paired Sample T-Test to analyze the difference in blood glucose levels before and after the treatment. The normality of the data was tested by the Shapiro-Wilk test, while the homogeneity was tested by the Leven test. The results showed that the most effective ethanol extract of fragrant pandan leaves reduced blood glucose levels at a dose of 600mgkgBB by 26%, a dose of 400mgkgBB by 21%, a dose of 200mgkgBB by 18%, a positive control using glibenclamide 0.65mgkgBB as much as 10% and a negative control using CMC-Na by 3%.